1998
DOI: 10.1152/ajpcell.1998.274.6.c1496
|View full text |Cite
|
Sign up to set email alerts
|

SNAP-25 is essential for cortical granule exocytosis in mouse eggs

Abstract: Synaptosome-associated protein of 25 kDa (SNAP-25) has been shown to play an important role in Ca2+-dependent exocytosis in neurons and endocrine cells. During fertilization, sperm-egg fusion induces cytosolic Ca2+mobilization and subsequently Ca2+-dependent cortical granule (CG) exocytosis in eggs. However, it is not yet clear whether SNAP-25 is involved in this process. In this study, we determined the expression and function of SNAP-25 in mouse eggs. mRNA and SNAP-25 were detected in metaphase II (MII) mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 27 publications
0
26
1
Order By: Relevance
“…Both mRNA and protein exist in MII mouse eggs. After microinjection of an outline neurotoxin A (Bunt/A), which selectively cleaves SNAP-25, sperm-induced CG exocytosis is significantly inhibited, and the inhibition is attenuated by co-injection of SNAP-25, suggesting that SNAP-25 may be involved in Ca 2ϩ -dependent CG exocytosis during fertilization in mouse eggs (Ikebuchi et al, 1998).…”
Section: G-proteinsmentioning
confidence: 99%
“…Both mRNA and protein exist in MII mouse eggs. After microinjection of an outline neurotoxin A (Bunt/A), which selectively cleaves SNAP-25, sperm-induced CG exocytosis is significantly inhibited, and the inhibition is attenuated by co-injection of SNAP-25, suggesting that SNAP-25 may be involved in Ca 2ϩ -dependent CG exocytosis during fertilization in mouse eggs (Ikebuchi et al, 1998).…”
Section: G-proteinsmentioning
confidence: 99%
“…Several studies have shown that exocytosis in gametes is controlled by interactions between specific sets of proteins that belong to the SNARE (soluble N-ethylmaleimide-sensitive factor attachment protein receptor) protein family [12][13][14]. Functional studies in mouse oocytes have provided solid evidence that SNAP25 is involved in the CR [13].…”
Section: Introductionmentioning
confidence: 99%
“…Functional studies in mouse oocytes have provided solid evidence that SNAP25 is involved in the CR [13]. However, scarce information is available on the (re)localization of SNARE proteins during specific stages of oocyte development, maturation, and fertilization.…”
Section: Introductionmentioning
confidence: 99%
“…In mouse eggs, SNAP-25 is cortically localized, and Botulinum toxin A (which targets SNAP-25) inhibited CG exocytosis [93].…”
Section: Docking and Fusion: Sharing The Snaresmentioning
confidence: 99%